How to Build a Mile-High Skyscraper. - Jones, W.D.
Behemoth buildings are becoming practical thanks to new technologies and innovations in construction materials. This paper presents the use of different innovative technologies in the construction of mile-high skyscrapers
Keywords: Carbon nanotubes; Concrete technology; Construction materials; Elevator technology; Energy efficiency; Green technology; Innovative technologies; Mile-high skyscrapers; Safety technology; Smart fibres